Dietary supplementation of Bacillus cereus as probiotics in Pengze crucian carp (Carassius auratus var. Pengze): Effects on growth performance, fillet quality, serum biochemical parameters and intestinal histology. (10th May 2019) - Yang, Gang; Cao, Hongzhong; Jiang, Wenhao; Hu, Baoqing; Jian, Shaoqing; Wen, Chungen; Kajbaf, Kimia; Kumar, Vikas; Tao, Zhiying; Peng, Mo
Abstract: This study was aimed to evaluate the effects of dietary supplementation of Bacillus cereus as probiotics on growth, fillet quality, serum biochemical parameters and intestinal histology of Pengze crucian carp ( Carassius auratus var. Pengze). Fish were fed basic diet (Control group) and three diets such as CD7, CD9 and CD11 supplemented with B. cereus at dose of 10 7, 10 9 and 10 11 CFU/kg for 70 days. The results showed that supplementation of 10 9 CFU/kg B. cereus significantly improved the growth performance compared to that in the Control group. The textures of muscle were improved by dietary supplementation of probiotics, and the hardness, gumminess, chewiness and the resilience of fish fillet increased with increasing dose of B. cereus . Total cholesterol including high‐density lipoprotein and low‐density lipoprotein level in serum decreased correspondingly with increasing level of probiotics whereas, acid phosphatase and catalase activities increased in serum. B. cereus supplementation enhanced the immunity and antioxidant capacity via an increase in acid phosphatase, alkaline phosphatase, glutathione peroxidase, reduce glutathione, and catalase, accompanied by a significant reduction in malondialdehyde. Higher intestinal fold height was observed in CD9 group than other groups. The lowest enterocyte height was exhibited in the Control group, HE values increased with increasing dose of probiotics. Moreover, dietary inclusion of B. cereus significantly affected the digestive enzymes activities in terms of higher lipase and trypase activities. In conclusion, dietary supplementation of B. cereus could promote the growth, elevate the immunity and antioxidant status of carp, and importantly improve the texture of fish fillet.